Systematic review of the relation between smokeless tobacco and non-neoplastic oral diseases in Europe and the United States - Weitkunat Rolf; Kallischnigg Gerd; Lee Peter N (BMC, 2008)
Abstract Background How smokeless tobacco contributes to non-neoplastic oral diseases is unclear. It certainly increases risk of oral mucosal lesions, but reviewers disagree as to other conditions. In some areas, especially South-East Asia, risk is difficult to quantify due to the many products, compositions (including non-tobacco ingredients), and usage practices involved. This review considers studies from Europe (in practice mainly Scandinavia) and from the USA. Methods Experimental and epidemiological studies published in 1963-2007 were identified that related risk of oral lesions to smokeless tobacco use. Data were assessed separately for oral mucosal lesions, periodontal and gingival diseases, dental caries and tooth loss, and oral pain. Results Oral mucosal lesions: Thirty-three epidemiological studies consistently show a strong dose-related effect of current snuff on oral mucosal lesion prevalence. In Scandinavia, users have a near 100% prevalence of a characteristic "snuff-induced lesion", but prevalence of the varied lesions reported in the USA is lower. Associations with chewing tobacco are weaker. The lack of clear association with former use suggests reversibility following cessation, consistent with experimental studies showing rapid lesion regression on quitting. Periodontal and gingival diseases: Two of four studies report a significant association of snuff with attachment loss and four out of eight with gingival recession. Snuff is not clearly related to gingivitis or periodontal diseases. Limited evidence suggests chewing tobacco is unrelated to periodontal or gingival diseases. Tooth loss: Swedish studies show no association with snuff, but one US study reported an association with snuff, and another with chewing tobacco. Dental caries: Evidence from nine studies suggests a possible relationship with use of smokeless tobacco, particularly chewing tobacco, and the risk of dental caries. Oral pain: Limited evidence precludes any clear conclusion. Conclusion This review confirms the strong association of current use of smokeless tobacco, particularly snuff, with prevalence of oral mucosal lesions. It provides suggestive evidence of an association of snuff use with gingival recession and attachment loss, and of chewing tobacco with dental caries. While smokeless tobacco clearly increases risk of oral mucosal lesions, interpretation for other endpoints is limited by study weaknesses, including poor confounding control.